2006
DOI: 10.1080/14767050600850381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal dexamethasone and alpha-ketoglutarate administration on skeletal development during the last three weeks of prenatal life in pigs

Abstract: The bone mineral density and mechanical and geometric properties of humeri indicate an inverse effect of maternal separate or simultaneous administration of AKG and Dex to sows on bone development during the last 24 days of prenatal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Original Article stress and excess glucocorticoid on fetal skeletal development, and on skeletal growth and bone mineralization after birth as a long-term effect (Swolin-Eide et al, 2002;Śliwa et al, 2006;Lee et al, 2008;Choe et al, 2011). However, there is still no coherent connection between a specific type of stressor and the concomitant skeletal changes.…”
Section: A Few Studies Have Demonstrated the Effect Of Prenatalmentioning
confidence: 99%
See 2 more Smart Citations
“…Original Article stress and excess glucocorticoid on fetal skeletal development, and on skeletal growth and bone mineralization after birth as a long-term effect (Swolin-Eide et al, 2002;Śliwa et al, 2006;Lee et al, 2008;Choe et al, 2011). However, there is still no coherent connection between a specific type of stressor and the concomitant skeletal changes.…”
Section: A Few Studies Have Demonstrated the Effect Of Prenatalmentioning
confidence: 99%
“…Maternal restraint stress or DEX exposure in animal models resulted in vertebral and sternal abnormalities, and the retardation of somite and limb formation (Śliwa et al, 2006;Lee et al, 2008;Choe et al, 2011). Several human studies have demonstrated that prenatal GC treatment led to a transient suppression of the levels of carboxy-terminal propeptide of type I collage (PICP) and carboxy-teminal telopeptide of type I collagen (ICTP), a measure to assess the rate of bone formation and resorptive, respectively, but with no long-term impact (Korakaki et al, 2007;Korakaki et al, 2011).…”
Section: Effect Of Prenatal Dex Treatment On the Protrusion Of Xiphoimentioning
confidence: 99%
See 1 more Smart Citation
“…There were 78 children (49 boys and 29 girls) who met the criteria of Peterson [25] for GPs (prevalence = 29.9%). The children’s demographics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is recognized from animal-based and clinical studies that perinatal risk factors including gestational age [17,18], birth length [18,19], birth weight [19,20] and maternal smoking or ethanol consumption [21] as well as the antenatal use of corticosteroids [18,22,23,24,25], contribute towards alterations in a newborn’s bone metabolism having a direct impact on the mineralization of osteoid tissue during infancy. As the skeletal development is strongly related with bone changes during fetal and newborn periods, evaluation of the factors influencing mineral metabolism during early childhood can lead to useful conclusions about skeletal functionality in later life.…”
Section: Introductionmentioning
confidence: 99%